Novel reaction of the “huisgen zwitterion” with chalcones and dienones: an efficient strategy for the synthesis of pyrazoline and pyrazolopyridazine derivatives - Nair, Vijay; Biju, Akkattu T.; Mathew, Smitha C.; Eringathodi, Suresh (Angewandte Chemie-International Edition, 2007)
Two unexpected transformations: The reaction of the Huisgen zwitterion derived from triphenylphosphane and diisopropyl azodicarboxylate (DIAD) with chalcones affords functionalized pyrazolines. In contrast, the reaction with dienones affords pyrazolopyridazines, presumably by Diels–Alder reaction of the initially formed pyrazoline with excess DIAD (see scheme).
Keywords: chalcones; nitrogen heterocycles; pyrazolines; synthetic methods; zwitterions

Reaction of huisgen zwitterion with diaryl-1,2-diones and ketones: an efficient protocol for carbon-nitrogen bond formation - Nair, Vijay; Biju, Akkattu T.; Mathew, Smitha C. (Synthesis-Stuttgart, 2007)
The reaction of Huisgen zwitterion, derived from triphenylphosphine and dialkyl azodicarboxylate, with diaryl-1,2-diones afforded N,N-dicarboalkoxy monohydrazones via a mechanistically novel rearrangement. Cyclic and acyclic ketones furnished vinyl hydrazinedicarboxylates under similar conditions.
Keywords: betaines - diazo compounds - hydrazones - ketones - rearrangements

Reaction of tpp-azodicarboxylate zwitterions and aldehydes: unprecedented synthesis of acyl carbamates - Nair, Vijay; Mathew, Smitha C.; Biju, Akkattu T.; Eringathodi, Suresh (Tetrahedron Letters, 2007)
An efficient synthesis of acyl carbamates from aryl aldehydes by the reaction of triphenylphosphine and dialkyl azoesters is described.

Carbon-nitrogen bond-forming reactions of dialkyl azodicarboxylate: a promising synthetic strategy - Nair, Vijay; Biju, Akkattu T.; Mathew, Smitha C.; Pattoorpadi, Beneesh Babu (Chemistry an Asian Journal, 2008)
Azodicarboxylates have found applications in electrophilic amination reactions and in pericyclic reactions. The nucleophilic trigger in Mitsunobu reactions, that is, the zwitterion formed from triphenylphosphine and dialkyl azodicarboxylate, has been utilized recently in various heterocyclic constructions. This Focus Review summarizes the potential utility of azodicarboxylates in various carbon–nitrogen bond-forming reactions.
Keywords: amination reactions; azodicarboxylates; C[BOND]N bond formation; heterocycles; Huisgen zwitterion

Reaction of huisgen zwitterion with diaryl ketones leading to the facile synthesis of mono- and bis(alkoxycarbonyl)hydrazones - Nair, Vijay; Mathew, Smitha C.; Biju, Akkattu T.; Eringathodi, Suresh (Synthesis-Stuttgart, 2008)
The Huisgen zwitterion, generated from triphenylphosphine and dialkyl azodicarboxylates, afforded upon reaction with diaryl ketones both mono- and bis(alkoxycarbonyl)hydrazones, depending on the reaction conditions.

Reactions of morita-baylis-hillman acetates with huisgen zwitterions: a novel strategy for the synthesis of ?-amino acid derivatives - Jose, Anu; Paul, Rony Rajan; Mohan, Resmi; Mathew, Smitha C.; Biju, Akkattu T.; Eringathodi, Suresh; Nair, Vijay (Synthesis, 2009)
The reaction of Huisgen Zwitterion with Morita–Baylis– Hillman acetates afforded b-amino acid derivatives.
Keywords: b-amino acid; Huisgen zwitterion; Morita–Baylis–Hillman acetate